2016
DOI: 10.1370/afm.1933
|View full text |Cite
|
Sign up to set email alerts
|

Interconception Care for Mothers During Well-Child Visits With Family Physicians: An IMPLICIT Network Study

Abstract: PURPOSE Interconception care (ICC) is recommended to improve birth outcomes by targeting maternal risk factors, but little is known about its implementation. We evaluated the frequency and nature of ICC delivered to mothers at well-child visits and maternal receptivity to these practices. METHODSWe surveyed a convenience sample of mothers accompanying their child to well-child visits at family medicine academic practices in the IMPLICIT (Interventions to Minimize Preterm and Low Birth Weight Infants Through Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
1
23
0
2
Order By: Relevance
“…care provided between pregnancies, and that a specific role could be assigned to youth healthcare physicians providing preventive child healthcare. The potential of interconception care to new mothers is increasingly being discussed in the literature, and it is stated that its unique position to reach women and its expertise in preventive healthcare are facilitating factors [ 37 , 38 ]. However, a disadvantage could be that in some cases, parents have already been confronted with the birth of an affected child without being aware of their increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…care provided between pregnancies, and that a specific role could be assigned to youth healthcare physicians providing preventive child healthcare. The potential of interconception care to new mothers is increasingly being discussed in the literature, and it is stated that its unique position to reach women and its expertise in preventive healthcare are facilitating factors [ 37 , 38 ]. However, a disadvantage could be that in some cases, parents have already been confronted with the birth of an affected child without being aware of their increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…19 The IMPLIC-IT network has demonstrated that well-child visits in family medicine clinics can be used to identify and support high-risk mothers and children 20 and that mothers are interested in health advice from their child's physician even if they receive their health care from a different provider. 21 Enhancing the knowledge base of PDs on these approaches may be one avenue to promote change given the association we found between the self-reported knowledge of PDs on this topic and the comprehensiveness of the approach to resident training on this topic. A limitation is that our study relied on PD report to describe the training and clinical experiences of residents.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, other studies focusing on the promotion of folic acid supplementation in routine PCHC practice have shown promising results with regards to increased use and intention [18, 19]. Other encouraging, recently reported, ICC related practices that were aimed at mothers during well-child visits, include screening and addressing tobacco use, depression risk and contraception use [39, 40]. As such, standardization of certain ICC items in PCHC could make it accessible for all women while warranting sufficient management support and resources, which could improve feasibility.…”
Section: Discussionmentioning
confidence: 99%